Effectiveness of Roy’s Adaptation Model-Based Interventions in Nursing Research: A Systematic Review - Idyatul Hasanah; Apriani Susmita Sari; Dina Alfiana Ikhwani (An Idea Health Journal, 2026)
Background: Roy’s Adaptation Model (RAM) conceptualizes individuals as adaptive systems that respond to environmental changes through coping mechanisms to maintain equilibrium. This model has been extensively applied as a theoretical framework in nursing practice and research to enhance the quality of care. The present study assessed the efficacy of Roy’s Adaptation Model in guiding nursing research by analyzing recent publications that utilized RAM as a conceptual framework. Methods: A literature review design with a narrative synthesis approach was employed. Literature searches were conducted in five electronic databases: Scopus, PubMed, ProQuest, ScienceDirect, and SAGEPub, for articles published from 2017 to 2021. The selection process included identification, screening, and eligibility assessment based on predefined inclusion and exclusion criteria. Methodological quality was evaluated using appraisal tools from the Cochrane Collaboration and the Joanna Briggs Institute (JBI). Of the 1,315 articles initially identified, 20 studies met the inclusion criteria and were included in the analysis. Results: Most studies indicated that RAM-based interventions effectively improved patients’ adaptive responses, reduced anxiety levels and clinical symptoms, and enhanced quality of life. The reviewed studies encompassed diverse populations and healthcare settings. Interventions guided by Roy’s Adaptation Model consistently yielded positive outcomes, although variations in research methods and study designs affected the magnitude of reported effects. Conclusion: Roy’s Adaptation Model serves as an effective conceptual framework for developing nursing interventions across diverse healthcare settings.